Targeted next generation sequencing of MLH1-deficient, MLH1 promoter hypermethylated, and BRAF/RAS-wild-type colorectal adenocarcinomas is effective in detecting tumors with actionable oncogenic gene fusions - Vaňková, Bohuslava; Vaněček, Tomáš; Ptáková, Nikola; Hájková, Veronika; Dušek, Martin; Michal, Michael; Švajdler, Peter; Daum, Ondřej; Daumová, Magdaléna; Michal, Michal; Mezencev, Roman; Švajdler, Marián (Genes, chromosomes & cancer, 2020)
Oncogenic gene fusions represent attractive targets for therapy of cancer. However, the frequency of actionable genomic rearrangements in colorectal cancer (CRC) is very low, and universal screening for these alterations seems to be impractical and costly. To address this problem, several large scale studies retrospectivelly showed that CRC with gene fusions are highly enriched in groups of tumors defined by MLH1 DNA mismatch repair protein deficiency (MLH1d), and hypermethylation of MLH1 promoter (MLH1ph), and/or the presence of microsatellite instability, and BRAF/KRAS wild-type status (BRAFwt/KRASwt). In this study, we used targeted next generation sequencing (NGS) to explore the occurence of potentially therapeutically targetable gene fusions in an unselected series of BRAFwt/KRASwt CRC cases that displayed MLH1d/MLH1ph. From the initially identified group of 173 MLH1d CRC cases, 141 cases (81.5%) displayed MLH1ph. BRAFwt/RASwt genotype was confirmed in 23 of 141 (~16%) of MLH1d/MLH1ph cases. Targeted NGS of these 23 cases identified oncogenic gene fusions in nine patients (39.1%; CI95: 20.5%-61.2%). Detected fusions involved NTRK (four cases), ALK (two cases), and BRAF genes (three cases). As a secondary outcome of NGS testing, we identified PIK3K-AKT-mTOR pathway alterations in two CRC cases, which displayed PIK3CA mutation. Altogether, 11 of 23 (~48%) MLH1d/MLH1ph/BRAFwt/RASwt tumors showed genetic alterations that could induce resistance to anti-EGFR therapy. Our study confirms that targeted NGS of MLH1d/MLH1ph and BRAFwt/RASwt CRCs could be a cost-effective strategy in detecting patients with potentially druggable oncogenic kinase fusions.
Keywords: vysoce účinné nukleotidové sekvenování; Male; Receptor Protein-Tyrosine Kinases; lidé středního věku; protoonkogenní proteiny B-Raf; metylace DNA; senioři nad 80 let; Aged, 80 and over; Oncogene Proteins, Fusion; anaplastická lymfomová kináza; Humans; Adenocarcinoma; Middle Aged; senioři; NTRK; kolorektální nádory; mužské pohlaví; Female; colorectal cancer; tyrosinkinasové receptory; Aged; MutL homolog 1; protoonkogenní proteiny p21(ras); Proto-Oncogene Proteins p21(ras); promotorové oblasti (genetika); ALK; ženské pohlaví; genetické testování; Anaplastic Lymphoma Kinase; Colorectal Neoplasms; DNA Methylation; Adult; gene fusions; adenokarcinom; MutL Protein Homolog 1; Promoter Regions, Genetic; fúzní onkogenní proteiny; dospělí; lidé; BRAF; High-Throughput Nucleotide Sequencing; Proto-Oncogene Proteins B-raf; Genetic Testing